Effects of realimentation on small intestinal morphology and disaccharidase activity in malnutrition Sprague-Dawley rats (Faculty of Medicine Universitas Indonesia, 2006)
Low birth-weight infant and intrauterine growth retardation are still a health problem, especially in Indonesia due to high prevalence and need to be reduced. Malnutrition in infants are most common occur in low birth-weight infants. Malnutrition in rats resulted in hypotrophic and normoplastic mucosa of the small intestine. The finding was not only showed that small intestine was able to maintain its cell number in condition with restriction nutrient, however also suggested the posibility of epithelial regeneration if given adequate nutrient intake. Did realimentation recover the hypotrophic normoplastic mucosa to normotrophic normoplastic? The study aim to answer that question. Experimental animal study with post test-control group design was performed using 40 male litter of Sprague-Dawley rats, was fed standard chow. The study was divided into phases prenatally-induced malnutrition and continued with phase realimentation. The result of this study is the body weight, mucosal thickness, villus height, cryptus depth, ratio of villus/ crypt, number of villi, protein content, and disaccharidases of rats realimentation group was higher than non-realimentation group, but lower than control group. Prenatally-induced malnutrition did not reduced the population of small intestinal enterocytes. Realimentation in rats in prenatally-induced malnutrition was able to improve the hypotrophy of small intestinal mucosa and to increase the disaccharidases activities but did not reach the normal values. Realimentation in rats in prenatally-induced malnutrition was able to improve the maturity of small intestine mucosa but did not reach the normal values. The information will be helpfull to decide the policy of maternal malnutrition. (Med J Indones 2006; 15:208-16)Keywords: small intestinal morphology, disaccharidase activity, Sprague-Dawley rats, prenatally-induced malnutrition, realimentation.